2016
DOI: 10.3389/fmicb.2016.01750
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Evaluation of Bacteroides fragilis Protective Role against Bartonella henselae Liver Damage in Immunocompromised Murine Model

Abstract: Bartonella henselae is a gram-negative facultative intracellular bacterium and is the causative agent of cat-scratch disease. Our previous data have established that Bacteroides fragilis colonization is able to prevent B. henselae damages through the polysaccharide A (PSA) in an experimental murine model. In order to determine whether the PSA is essential for the protection against pathogenic effects of B. henselae in immunocompromised hosts, SCID mice were co-infected with B. fragilis wild type or its mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In a coinfection experiment, WT B. fragilis , but not the ΔPSA mutant, prevented uptake of B. henselae by endothelial progenitor cells. Furthermore, WT B. fragilis prevented B. henselae –induced tissue damage in a mouse model of coinfection, while the ΔPSA mutant failed to do so …”
Section: Polysaccharide Amentioning
confidence: 97%
See 1 more Smart Citation
“…In a coinfection experiment, WT B. fragilis , but not the ΔPSA mutant, prevented uptake of B. henselae by endothelial progenitor cells. Furthermore, WT B. fragilis prevented B. henselae –induced tissue damage in a mouse model of coinfection, while the ΔPSA mutant failed to do so …”
Section: Polysaccharide Amentioning
confidence: 97%
“…Although B. fragilis can contribute to intra‐abdominal abscess formation, soft tissue infections, and bacteremia when present outside the gut, it has many beneficial effects when contained within the gut—that is, in its normal habitat. Monocolonization of previously germ‐free mice with B. fragilis can correct cellular and developmental defects in the immune system, prevent intestinal inflammation in animal models of colitis, protect against infections, and even modulate immune responses in extraintestinal tisues …”
Section: The Gut Microfloramentioning
confidence: 99%
“…It has been observed that this bacterium plays a beneficial role in patients that suffer from IBD (Morgan and Harris, 2015 ). There is evidence that Bacteroides can be beneficial for maintaining the homeostasis in models of intra-abdominal sepsis and experimental colitis (Tzianabos et al, 1995 ; Pagliuca et al, 2016 ). This seems to be the case for B. fragilis , as its polysaccharide (PSA) induces IL-10 secretion by Tregs (Ochoa-Reparaz et al, 2010 ).…”
Section: What Do We Know About the Role Of The Microbiota In Non-intementioning
confidence: 99%
“…Bacteroides has been shown to produce many metabolites, such as short-chain fatty acids (SCFAs) [ 34 ] and polysaccharide A (PSA) [ 35 ]. Studies have shown that Bacteroides fragilis could protect against Bartonella henselae -induced liver damage through producing PSA [ 36 ]. SCFAs are derived from indigestible carbohydrates by the fermentation of gut microbiota and include compounds such as butyrate, propionate, and acetate [ 37 ].…”
Section: Discussionmentioning
confidence: 99%